Artificial Niches for Stromal Stem Cells as a Potential Instrument for the Design of the Surface of Biomimetic Osteogenic Materials; Russian Physics Journal; Vol. 56, iss. 10 - Khlusov I. A. Igor Albertovich; Khlusova M. Yu.; Pichugin V. F. Vladimir Fyodorovich; Sharkeev Yu. P. Yury Petrovich; Легостаева Е. В. Елена Викторовна (2014, 2014)
Title screen